Biology, movement behaviour and spatial dynamics of an exploited population of smooth hound shark mustelus mustelus around a coastal marine protected area in South Africa - da Silva, Charlene (Department of Biological Sciences, 2019)
Aspects of the life-history, movement in relation to a Marine Protected Area (MPA) boundary, and short and long-term spatial behaviour in relation to environmental preferences of Mustelus mustelus were studied in the Saldanha Bay region on the west coast of South Africa. The overarching aim of this thesis was to examine the biological and ecological circumstances under which a MPA could provide effective protection to a commercially caught coastal shark from fishing activity. The pigmentation, reproductive biology, diet, growth and maturity of Mustelus mustelus was examined from 217 ranging from 381 to 1734 mm TL and 467 to 1267 mm TL for females and males, respectively. Sharks in the bay represented the largest females and males recorded worldwide. The seasonal changes in oocytes and testes development, embryo length and the occurrence of near-term and postpartum females indicated that female parturition and ovulation occurs between November and December after a gestation period of 10-11 months. The presence of juveniles, neonates and pregnant females inside the Langebaan Marine Protected Area indicates it to be a nursery ground for this species. The largest part of the diet of M. mustelus consisted of three species of crustaceans: Hymenosoma orbiculare, Upogebia africana, Callichirus kraussi. No ontogenetic shift in diet was found for M. mustelus from Langebaan Lagoon. M. mustelus grow relatively rapidly, matured early (between 3 and 6 years) and attained a maximum observed age of 13 years. The movements of individual Mustelus mustelus in and adjacent to a small closed area (Langebaan Lagoon MPA, 34 km2 ) situated on the West Coast of South Africa were investigated over two years using acoustic telemetry. Sharks spent the majority of the time (in hours, average 79%) inside the Langebaan Lagoon MPA, and some sharks (n = 2 of 15 recorded during a full year) did not leave the reserve during the observation period. Time spent inside the closed area and the number of crossings of its boundary was strongly influenced by season. Sharks concentrated inside the closed area during summer, while they were widely distributed throughout the study area during winter months. A combination of shallow and sheltered waters in close proximity to the Saldanha Bay port and other boataccess points would normally make this summer aggregation highly vulnerable to fishing activity. The residency of M. mustelus within the closed area suggests that spatial protection may be effective for this species. Acoustic telemetry and in situ environmental data were used to investigate movement of M. mustelus in relation to changing environmental conditions over long (seasonal) and short (20 min) time scales. Results of Generalised Additive Mixed Modeling (GAMMs) indicated no significant influence of tide or moon phase and only a weak influence of diel period on movement and direction of movement. The thermal preference for M. mustelus was between 18 and 22 C as determined by GAMMS. Absolute temperature and the relative change in temperature at the shark’s position were the best predictors for shark movement and its direction in summer, explained 4.4 and 42.7 % of the deviance, respectively. This study provided evidence that M. mustelus inside the embayment decide their position within their area of residency according to their thermal preference and that temperature change constitutes the trigger that determines movement direction. This study confirms that M. mustelus are resident within the Saldanha embayment and distinct by diet, life-history parameters and colouration from stocks elsewhere. M. mustelus from this group are more fecund and larger in body size than those from all other populations globally, possibly due to the favourable temperature conditions in the warm sheltered lagoon and the existence of a MPA closed to fishing which includes preferred habitat for all life- IX history stages of this species. In the absence of a comprehensive stock assessment and species-specific management, well-positioned closed areas that include preferred habitat can aid the sustainability of coastal shark fisheries.